Implementasi Sistem Informasi Pemerintah Daerah: Apakah Efektif Dalam Mendukung Pelaporan Keuangan OPD (Jurnal Kendali Akuntansi, 2024)
This study aims to determine how effective the implementation of local government information systems (SIPD) in supporting financial reporting at OPDs in Mataram City, namely RSUD X. This research uses descriptive qualitative methods with data collection techniques in the form of observations and interviews. The research analysis refers to the UTAUT effectiveness indicators consisting of Performance Expectancy, Effort Expectancy, Social Influences and Facilitating Conditions. The results of this study indicate that the implementation of SIPD in supporting financial reporting at RSUD X when viewed in terms of indicators of performance expectancy, effort expectancy and facilitating conditions is still less effective because in its implementation SIPD still has many weakness both in terms of system stability and the availability of features needed, while for indicators of social influences SIPD can already be categorized as effective because the implementation of financial report data entry is adapted to user needs.